Organization of biological materials collection on study of the natural prototype of babesious infection - Torianyk, Inna (ScienceRise: Medical Science, 2021)
Ukraine's enzootic in accordance with natural focal diseases including babesiosis, makes the research undertaken relevant. Aim of the study: to determine the stages in organising the collection of biological materials in the study of the natural prototype of babesiosis. Materials and methods of research. Objects were murine rodents of Muridae family of genera Myodes, Microtus, Apodemus, Sylvaemus of natural habitats of forest-steppe zone of Ukraine, their ectoparasites-carriers of babesiosis - ticks of family Ixodidae. Collection, accumulation and registration of biological materials was carried out in the conditions of scientific expeditions. Regional geography of them concerned Volyn, Zhytomyr, Kyiv, Poltava, Sumy, Kharkiv, Chernihiv regions of Ukraine. Results. A total of 63 wild rodents were captured and used in the study. They were adult mice of both sexes, weighing 45-90 g, belonging to the Muridae family, genera Myodes, Microtus, Apodemus, Sylvaemus. Each group of animals gravitated to a specific geographical area of existence with appropriate attributes of flora and fauna. Collection and recording of those on rodent-feeding animals showed that Ixods differ according to phases of development, blood feeding, sex attributes and species affiliation. Conclusions. Nosological profile of babesiosis as a natural focal obligate-transmissible protozoan blood parasitosis determined methodology of epizootic assessment of area, natural prototype of disease, collection of biological material samples (BMS). BMS collection activities for babesiosis are seasonally dependent. Conducted researches should be focused on 3 links of epizootic or epidemic chain of babesiosis. Invasion by babesia ticks in optimal natural-climatic conditions of development, annual contact with animals led to formation of a latent focus of babesiosis